2020
DOI: 10.1097/inf.0000000000002821
|View full text |Cite
|
Sign up to set email alerts
|

Probable Vertical Transmission of SARS-CoV-2 Infection

Abstract: Background: To date, although neonatal infections with severe acute respiratory syndrome coronovirus 2 (SARS-CoV-2) have been described, none of these have been proven to be the result of vertical transmission of SARS-CoV-2. Methods: We describe the probable vertical transmission of SARS-CoV-2 in a neonate born to a mother with coronavirus disease 2019 (COVID-19). Results: Following cesarean section, the neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 13 publications
2
31
0
1
Order By: Relevance
“…Clinical features of neonatal SARS-CoV-2 infections. Ninetyseven neonates presented with clinical features related to COVID-19: 18,20,[26][27][28]30,32,[34][35][36][38][39][40][41]44,45,[50][51][52]55,56,58,60,61,[65][66][67][70][71][72]77,78,80,81,[85][86][87][88]90 their distribution is shown in Table 3. Respiratory manifestations mainly consisted of signs of respiratory failure, such as tachypnoea, intercostal retractions, and rhinitis; neonatal ARDS was not diagnosed in any case.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical features of neonatal SARS-CoV-2 infections. Ninetyseven neonates presented with clinical features related to COVID-19: 18,20,[26][27][28]30,32,[34][35][36][38][39][40][41]44,45,[50][51][52]55,56,58,60,61,[65][66][67][70][71][72]77,78,80,81,[85][86][87][88]90 their distribution is shown in Table 3. Respiratory manifestations mainly consisted of signs of respiratory failure, such as tachypnoea, intercostal retractions, and rhinitis; neonatal ARDS was not diagnosed in any case.…”
Section: Resultsmentioning
confidence: 99%
“…Ninety-seven neonates presented with clinical features related to COVID-19: 18 , 20 , 26 28 , 30 , 32 , 34 – 36 , 38 41 , 44 , 45 , 50 – 52 , 55 , 56 , 58 , 60 , 61 , 65 67 , 70 72 , 77 , 78 , 80 , 81 , 85 – 88 , 90 their distribution is shown in Table 3 . Respiratory manifestations mainly consisted of signs of respiratory failure, such as tachypnoea, intercostal retractions, and rhinitis; neonatal ARDS was not diagnosed in any case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to study other possible long-term effects on male and female gametes , speci cally whether there might be shedding of virus in some individuals that might even affect the safety and storage of gametes 18 . Evidence continues to emerge regarding effects of the novel coronavirus in pregnancy and some initial reports suggest that complications, particularly after delivery, may be increased 9 , even if outcomes for infants are largely reassuring when considering potential effects of SARS-CoV-2 infection acquired before or during birth 5,25 . Further studies are necessary, and additional data regarding outcomes of early pregnancies in demonstrated infected pregnant women should be collected 26 .…”
Section: Resultsmentioning
confidence: 99%
“…5, Cases of suspected congenital SARS-CoV-2 infection have also been reported. [13][14][15] These authors recommended blood, nasopharyngeal, placenta and umbilical cord testing as soon as possible after birth, after a thorough cleansing of the newborn. This would help to establish the overall risk of COVID-19 infection due to in-utero or perinatal exposure.…”
Section: Discussionmentioning
confidence: 99%